Mucosa-adherent Pediococcus Pentosaceus I44 isolated from healthy human and effect of oleic acid on its probiotic properties - Lavanya Vasudevan; Jayanthi V; Srinivas M; Chandra TS (Current Research in Microbial Sciences, 2021)
With the aim of selectively isolating and understanding the cultivable lactic acid bacteria that are autochthonous to human gut, biopsy samples were collected from the terminal ileum and caecum of healthy volunteers who underwent routine colonoscopy procedure. The use of tissue samples (over stool samples) provides for a better expression of the autochthonous bacterial population of the human gut. The strains that were stable after many rounds of sub-culture were identified and studied further. One such ileal isolate, a Gram-positive, catalase-negative cocci was identified to be Pediococcus pentosaceus I44. It was studied for its gastric tolerance, bile tolerance and surface properties, and reported here. The effect of tween-80, oleic acid, extra virgin olive oil and sesame oil on the aforementioned properties of P. pentosaceus I44 was also analysed. The isolate was able to survive well in simulated gastric fluid of pH 3.0 followed by treatment in simulated intestinal fluid with a survival percentage of around 70%. It was, however, unable to withstand pH 2.0 even in the presence of supplements. It showed good tolerance to bile stress (1% w/v), and its cell surface was found to be hydrophilic. P. pentosaceus I44 showed good aggregation of 87% after 24 h, with oleic acid having a significant effect on the isolate's aggregation potential. P. pentosaceus I44 is one of the few mucosa-bound cultivable bacteria that are adapted for survival in human colon. Studying and analysing such isolates might provide useful insights into their role in metabolism and health.